Active H3K27me3 demethylation by KDM6B is required for normal development of bovine preimplantation embryos. Issue 12 (2nd December 2017) - Chung, Nhi; Bogliotti, Yanina S.; Ding, Wei; Vilarino, Marcela; Takahashi, Kazuki; Chitwood, James L.; Schultz, Richard M.; Ross, Pablo J.
ABSTRACT: The substantial epigenetic remodeling that occurs during early stages of mammalian embryonic development likely contributes to reprogramming the parental genomes from a differentiated to a totipotent state and activation of the embryonic genome. Trimethylation of lysine 27 of histone 3 (H3K27me3) is a repressive mark that undergoes global dynamic changes during preimplantation development of several species. To ascertain the role of H3K27me3 in bovine preimplantation development we perturbed the activity of KDM6B, which demethylates H3K27me3. Knockdown of maternal KDM6B mRNA inhibited the reduction in global levels of H3K27me3 from 2-cell to 8-cell embryo stages and compromised development to the blastocyst stage; embryos that developed to the blastocyst stage had fewer inner cell mass (ICM) and trophectoderm (TE) cells. In addition, the transcriptome of KDM6B knockdown embryos was altered at the 8-cell stage and characterized by downregulation of transcripts related to transcriptional regulation, chromatin remodeling, and protein catabolism. Inhibiting the catalytic activity of KDM6B with a specific small molecule inhibitor also prevented the global decrease in H3K27me3 and compromised development to the blastocyst stage. These results indicate that histone demethylation activity, mediated by KDM6B, is required for the global decrease in H3K27me3, correct activation of the embryonic genome, and development to the blastocyst stage in bovine embryos.